PERAN KRITERIA PENILAIAN DARI IDE KREATIF TERHADAP PERFORMA INOVASI DI UNIVERSITAS TARUMANAGARA - ian Nurparia Suryawan, Yenny Lego, Richard Andrew (Jurnal Manajemen, 2017)
The research conducted by this writing team aims to make a study of the selection of ideas that are relevant to innovation management by combining an array of assessment criteria that can be used to identify initial product ideas with the potential for innovation. In this case the researcher develops a framework that is integrated with a theoretical perspective derived from the literature of innovation and creativity. In the creativity literature, insight into novelty and usefulness is studied, while in the innovation literature, insights into novelty and market potential are studied. The results of the framework include the novelty of ideas and product usability with a clear focus on increasing company value through potential markets. This criterion that allows the incorporation of creative ideas for new products with potential innovation performance. In this study also, researchers made an assessment of several Tarumanagara University students based on the peculiarities of the three criteria by always supporting the independent role of each criterion in assessing potential innovations. The results of the study show that novelty, usefulness and market potential are very closely related to the performance of innovation and therefore the assessment criteria must be used so that the performance of innovation from Tarumanagara University in particular and the world community in general is maintained. Researchers hope that the students studied can explain the relevance of each unique criterion and relationship within the framework.Â Keywords: Innovation, Assessment, and Creative Ideas